2005
DOI: 10.1159/000087297
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Homocysteine Levels and Development of Alzheimer’s Disease in Mild Cognitive Impairment Patients

Abstract: The aim of this study was to investigate over a 3-year period the connection between homocysteine (Hcy) levels and development of Alzheimer’s disease (AD) in patients with mild cognitive impairment (MCI). Hcy was analyzed in 68 men, mean age 65 years, and 68 women, mean age 64 years. Age, sex, cobalamin, folate, creatinine, and thyroid profiles as well as results of Mini-Mental State Examination at the first visit to the memory investigation unit of a geriatric department were recorded from patient journals co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Plasmatic levels of homocysteine tend to be higher in converters than in non-converters with possible protective effect in MCI patients having low or normal levels [112].…”
Section: Blood and Csf Biomarkersmentioning
confidence: 96%
“…Plasmatic levels of homocysteine tend to be higher in converters than in non-converters with possible protective effect in MCI patients having low or normal levels [112].…”
Section: Blood and Csf Biomarkersmentioning
confidence: 96%
“…However, plasma tHcy concentration was rather normal in our previous studies of this group of patients [4][5] and several recent works reported both normal [15] and elevated [16,17] plasma tHcy in patients with MCI. Furthermore, elevated plasma tHcy in these patients has been associated with the development of cognitive impairment [18,19] . The main objective of the present study was to further investigate the association between plasma tHcy concentration and vascular disease in elderly patients with objectively confirmed memory complaints, thus fulfilling the criteria of MCI [20] .…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of the present study was to further investigate the association between plasma tHcy concentration and vascular disease in elderly patients with objectively confirmed memory complaints, thus fulfilling the criteria of MCI [20] . Since a high transition of patients with MCI to Alzheimer's disease (AD) has been reported [18,21,22] , we also included a group of patients with AD in the present study. The concentration of plasma tHcy was related to the presence of vascular disease, based on history and/or symptoms of vascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…One observational study found that a low/normal tHcy level appeared to reduce the risk of progression of mild cognitive impairment to AD [29] . Two prospective studies showed that high tHcy levels were related to an increased risk of dementia and AD [30,31] .…”
mentioning
confidence: 99%